Methodological recommendations for teachers to form concepts related to the diamond vocabulary category in elementary school students. (Journal of Pedagogical Inventions and Practices, 2022)
This article provides methodological recommendations for primary school teachers on the formation of competencies related to rhyming words in students. There is also a special emphasis on the concept of competence in education